Functional isoDNA aptamers: modified thrombin binding aptamers with a 2'-5'-linked sugarphosphate backbone (isoTBA) - Gunjal, Anita D.; Fernandes, Moneesha; Erande, Namrata D.; Rajamohanan, P. R.; Kumar, Vaijayanti A. (Chemical Communications, 2014)
The regioisomeric 3'-deoxy-2'-5'-linked thrombin binding DNA aptamers (isoTBAs) were chemically synthesized and their ability to form unimolecular anti-parallel G-quadruplexes in the presence of K+ ions was evaluated. These modified sequences retain the function of the native thrombin binding aptamer (TBA), exhibit better stability against exonuclease and are capable of slowing down the process of blood clotting.

Favorable 2 '-substitution in the loop region of a thrombin-binding DNA aptamer - Awachat, Ragini; Wagh, Atish A.; Aher, Manisha; Fernandes, Moneesha; Kumar, Vaijayanti A. (Bioorganic & Medicinal Chemistry Letters, 2018)
Simple 2'-OMe-chemical modification in the loop region of the 15mer G-rich DNA sequence GGTTGGTGTGGTTGG is reported. The G-quadruplex structure of this thrombin-binding aptamer (TBA), is stabilized by single modifications (T -> 2'-OMe-U), depending on the position of the modification. The structural stability also renders significantly increased inhibition of thrombin-induced fibrin polymerization, a process closely associated with blood-clotting. (C) 2018 Elsevier Ltd. All rights reserved.